DEGRADATION OF REEF FISH CATCH AS AN EFFECT OF TOURISM INDUSTRY ACTIVITIES IN GILI SULAT AND GILI LAWANG WATERS, EAST LOMBOK - . Mustaruddin; Lalu R. T. Savalas; Pandu Saptoriantoro (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
The development of tourism activities in industrial scale since 2004 in the region of Gili Sulat and Gili Lawang have caused problem to local fishermen for catching reef fish. The objective of this research was to analyse the preeminent fishing gears of reef fish, the contamination types of tourism industries to fishing ground, and the degradation pattern of reef fish catch as an effect of tourism industry activities. The method used in this research was scoring method, quality standard test of water to fishery activities, and exponential regression model. The results showed that preeminent fishing gears of reef fish in the region of Gili Sulat and Gili Lawang were handline (Fgab = 2.000) and fish trap (Fgab = 1.556). The contamination types of tourism industries which bothering fishing ground of reef fish were total suspended solid (TSS), garbage, detergent, and timbal (Pb). The degradation pattern in quantity of reef fish catch (Y1) by activities of tourism industry (X) was formulated with moel Y1 = 31.574e-0.305X (R2=0.403, p=0.000). The degradation pattern of reef fish catch by activities of tourism industry (X) in the form of value of reef fish catch (Y2) and figuring waste in reef fishing (Y3) was formulated with model Y2=474823e-0.236X (R2=0.206, p=0.012), and Y3=1.296e0.329X (R2=0.071, p=0.156).